Optical design and fabrication of a common-aperture multispectral imaging system for integrated deep space navigation and detection. (August 2023) - Cao, Jiajing; Chang, Jun; Huang, Yi; Wu, Yunan; Ji, Zhongye; Lai, Xiaoxiao; Wang, Junya; Li, Yiting; Zhu, Weihong; Li, Xuyang
Abstract: Multispectral imaging systems enable the simultaneous acquisition of spatial and multispectral information about a target, thereby improving the capability of all-weather autonomous spacecraft operations for sensing measurements and condition identification. This paper reports designing and constructing a common-aperture multispectral imaging system (CAMIS) that can simultaneously obtain ultraviolet, visible, mid-wave, and long-wave infrared wavebands. Such a system can simultaneously realize distant stars' navigation and multispectral detection. An experimental setup was constructed to verify the basic principles of the device. The device is used to image an optical-resolution target and a pinhole. The results indicated that the system could perform celestial navigation in the visible waveband and image objects well in multiple wavebands, thereby realizing the integration of deep-space navigation and detection.